Diagnosis of leaf nutrient content for ‘common’ arrowroot plants fertilized with ovine manure (Research, Society and Development, 2022)
Despite arrowroot’s (Maranta arundinaceae L.) appeal in several industry sectors, which indicates high potential for large-scale production, few studies have investigated the nutritional status of this crop species. Given the economic relevance of the crop and the limited data in the literature, the objective of this work was to evaluate the nutritive effect of the ovine biofertilizer in the cultivation of arrowroot ‘comum’, in two evaluation periods 180 and 272 days after planting (DAP). The experiment was laid out as a split-plot randomized complete block design with four replicates. Leaf contents of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulfur (S), iron (Fe), zinc (Zn), copper (Cu), manganese (Mn), boron (B), and sodium (Na) were determined. High K and Na contents were observed in arrowroot leaves. The sheep biofertilizer is suitable to meet the nutritional needs of arrowroot ‘common’. The continuous application of biofertilizer provided higher levels of nutrients at 272 days after planting.